Crafting a Digital Divide Index for Assessing Agricultural Disparities among Farmers: An Application of AHP Process - Chandra, Saurabh; Kalyan Ghadei (Indian Journal of Extension Education, 2024)
New measurement tool for assessing the digital divide disparity among farmers in e-agriculture was devised during 2023-24. The index comprises four dimensions, namely ICT ownership, awareness, accessibility, and usage, respectively. For dimension selection, the researchers employed the Analytic Hierarchy Process (AHP). The maximum eigen value (λ max) of the pairwise comparison matrix was 4.0049, serving as the overall weight for the decision-making process. In the item selection process, Likert-type scale procedures were used to assess statements for final indicator selection. An interview schedule with 45 indicators was administered to 60 farmers in a non-sampling area, with five ambiguous indicators subsequently removed. The digital divide index customized for farmers demonstrated strong reliability, with a split-half reliability coefficient of 0.846 (Spearman-Brown formula) and a Pearson correlation coefficient of 0.733. Internal consistency was good, as indicated by a Cronbach’s Alpha of 0.813, and the test displayed strong validity with a score of 0.919. Overall, these findings confirm the reliability and validity of the test in measuring the intended construct. Ultimately, the 38 items were consolidated into a standardized farmers’ digital divide index for assessing agricultural disparities in the farming community.